State Regulation of Forest Industrial Complex in Vietnam - Van Loc Nguyen (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article discusses the development of the forest industrial complex - one of the key sectors of the economy of the Socialist Republic of Vietnam which, to a great extent, defines the status and outlook of the Vietnamese economy in general. Development of the forest industrial complex is discussed in the context of fundamental socioeconomic reforms being implemented in Vietnam. Among other things they are aimed to attain one of the key backbone goals, i.e. defining the optimum balance between the state regulation and the initiative of economic subjects. The author touches endogenic and endogenic factors of the Vietnamese forest industrial complex development, including the natural-and-geographic factor, ethno-cultural traditions in economic activities, attraction of foreign investments. The author emphasizes both the achievements in the process of reforming the Vietnamese economy and unattained goals.